2021
DOI: 10.1016/j.childyouth.2021.106012
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of daytime sleepiness between problematic smartphone use and post-traumatic symptoms in COVID-19 home-refined adolescents

Abstract: Background COVID-19 was first recognized in late 2019 in China, at which time school closures forced most students to isolate at home or maintain social distance, both of which increased smartphone use, daytime sleepiness and post traumatic disorder (PTSD) risks. However, to date, no research has fully explored these behavioral risks or the consequences. Methods Two thousand and ninety home-confined students from two Chinese high schools participated in an online-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 76 publications
4
46
0
Order By: Relevance
“… 10 The high rate of smartphone addiction among the Bangladeshi students during the COVID-19 pandemic is concerning, as the prior studies have reported substantial consequences related to excessive smartphone use among students. 26–28 However, some of the reasons can explain such a higher PSU prevalence rate in the present study. For example, the participants who mandatorily attend online schooling might be responsible, as the previous study reported.…”
Section: Discussionmentioning
confidence: 56%
“… 10 The high rate of smartphone addiction among the Bangladeshi students during the COVID-19 pandemic is concerning, as the prior studies have reported substantial consequences related to excessive smartphone use among students. 26–28 However, some of the reasons can explain such a higher PSU prevalence rate in the present study. For example, the participants who mandatorily attend online schooling might be responsible, as the previous study reported.…”
Section: Discussionmentioning
confidence: 56%
“…A cross-sectional online survey conducted by Chen and colleagues showed that primary school children who had psychological distress during the COVID-19 outbreak might spend longer time on Internet-related activities (7). The relationship between PSU and psychological distress has been influenced by the COVID-19, which has been confirmed by Chen's another longitudinal Study (8). Some scholars identified the overuse of smartphones as a hidden crisis during the pandemic (9), and this issue has been highlighted by recent literatures in China.…”
Section: Introductionmentioning
confidence: 83%
“…This supports previous findings of a positive correlation between PTSD and mobile phone dependence ( Contractor et al, 2017 ). One possible reason for this association is that adolescents with PTSD tended to use mobile phones to constantly search for information related to the pandemic and watch pandemic-related videos, so as to gain the understanding of the pandemic and alleviate the unknown fear of the pandemic, and these behaviors make them fall into more serious mobile phone use ( Elhai et al, 2020 ; Hu et al, 2021 ). In addition, these adolescents with PTSD might resort to use mobile phones to escape the pressures of society, school, and family ( Yu and Wang, 2020 ), and regulate their emotions to increase positive emotions and reduce negative emotions, and maintain a balanced emotional state ( Contractor et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%